Towards an online dispute resolution mechanism for the Islamic finance industry: A preliminary literature survey - Oseni, Umar Aimhanosi; Omoola, Sodiq Olalekan (2013)
The growth and influence of the Internet on all spheres of human endeavour necessitated a revolutionary method of dispute resolution commonly referred to as Online Dispute Resolution (ODR). An increasing number of sectors have adopted online and electronic means of resolving disputes. ODR in financial and e-commerce services is of paramount importance to enable prompt and seamless dispute resolution platform for business-to-consumer (B2C) disputes in the Islamic finance industry. As a preliminary literature survey, this paper explores writings on ODR with the objective of tracking its development in the e-commerce sector. Specific reference is placed on writings focusing on developing ODR for consumer banking products peculiar to the Islamic finance industry. This study will adopt a quantitative and empirical method through a detailed survey using results of selected electronic search of online database. The result, when categorised across timeline, journals and sectors, shows that ODR is well suited for commercial and ethical banking. Thematic exposition of literature with the search term ‘Islamic banking’ and ‘ODR’ or ‘Online Dispute Resolution’ gives a low outcome which leads to the hypothesis that ODR researches related to Islamic finance is still in its embryonic stage. The paper concludes that current ODR models for consumer e-commerce can be well suited for the Islamic finance industry with some additional ethical considerations. There is a huge potential for ODR providers to tap into the large markets provided by the growing Sharī‘ah-compliant assets globally.